Cattle dung, phosphorus fertilizer and row planting on Centrosema pubescens (Benth) growth and, seed component attributes in ferralitic soils of Benin (West Africa) - HOUNDJO, DANIEL BIGNON MAXIME; ADJOLOHOUN, SÉBASTIEN; GBENOU, Basile; SAIDOU, ALIOU; AHOTON, Léonard; HOUINATO, MARCEL ROMUALD BENJAMIN; SINSIN, AUGUSTIN BRICE (My University, 2018)
Centrosema pubescens (Benth) is identified as a tropical forage legume of considerable promise which can improve pasture in West Africa. A study on the influence of rates of cattle manure in combination with plant row spacing on the growth, phenology and seed yield of Centro (Centrosema pubescens) was conducted at the Teaching and Research Farm of the Faculty of Agronomy Science of University of Abomey-Calavi in South Benin during 2014, 2015 and 2016 seasons. Five cattle manure rates (0, 4, 8, 12 and 16 tons/ha) and 40 kg P2O5/ha in combination with three plant spacings (40cm x 40cm, 80cm x 80cm, 120cm x 120cm) were evaluated in a 6x3 factorial laid out in Randomized Complete Block Design (RCBD). The growth and flowering characteristics measured in the field included: number of branches, number of leaves, plant girth, number of days to flower initiation, number of days to date of first flower appearance, number of days to 50% flowering, pod ripping time and efficiency of flower for pod production. Seed yield and seed components were evaluated each year by harvesting pods from 4 randomly selected plants per plot. Results obtained from data analysis showed that there was a significant influence of cropping season, row spacing, fertilizer rate and their three way interaction on seed production. Apart from the control treatment, seed yield was significantly higher in the second and third years (187.3 and 189.0 kg/ha, respectively) relative to the first year (153.8 kg/ha). Row spacing effect was significant on seed yield. Plants established at 80 cm × 80 cm gave significantly higher seed yield per ha (204.5 kg/ha) followed by 120 cm × 120 cm (179.0 kg/ha) and 40 cm × 40 cm (146.6 kg/ha) spacings. Seed yield was significantly increased due to application of cattle manure, with application of 12 tons/ha cattle manure giving higher yield. Neither row spacing nor fertilizer rate had significant effect on plant phenology. In contrast, efficiency of flower for seed production was influenced by fertilizer rate and cropping season. It can be concluded that row spacing of 80 cm × 80 cm and 12 tons per ha cattle manure can be recommended to farmers for C. pubescens seed production in the region
Keywords: organic fertilizer; plant density; growth; development; seed; West Africa